COMPARISON OF THE EFFECTIVENESS OF 3% DIQUAFOSOL AND 0,1 % HYALURONATE ACID IN DRY EYE DISEASE - Zulfikri Khalil Novriansyah (Bajang Institute, 2025)
A dry eye is a disease with morbidity on the ocular surface. Twenty-five percent of patients visiting the eye clinic complained of dry eye symptoms. In Indonesia, the prevalence of dry eye is reported to increase by 27,5% due to some related variables, including age, smoking, and pterygium (Lee AJ. et al., 2002). In Makassar, the case of dry eye is more often found in women than in men, with a ratio of 2:1 (Syawal, 2005). Most patients with dry eyes apply conventional conventional therapy, including supplementary lacrimal using a preserver. Unfortunately the long usage of supplements with preserver in active Ocular Surface Disorders has been reported to increase the vulnerability to toxicity (Gobbels M et al., 1992), (Wilson F et al., 1979). Therefore, it is necessary to carry out a study about the dry eye of patients using diquafosol. This study aims to measure the improvement in the ocular surface structure after administering topical diquafosol 3% based on the degree of dry eye disease. The study employed an experimental design, carried out at the Polyclinic of Dr. Wahidin Sudirohusodo and the University of Hasanuddin Education Hospitals, Makassar, for three months. The research population was patients with dry eyes doing examinations at the Polyclinic While the samples were patients fulfilling the inclusion criteria, including being diagnosed with dry eye, aged 18 years old, and willing to take part in the research by signing an informed consent. While the exclusion criteria are if the patients had allogeneic hematopoietic stem cell transplantation, had done refractive corneal surgery, were contact lens users, and had Stevens-Johnson syndrome and chemical / thermal burns; Have a history of allergies to drugs or health materials used in the study including artificial tears, Schirmer, fluorescein strips; and are possibly uncooperative during the examination. The samples were collected through random controlled trial sampling based on the target sample number (41). Data were recorded and analyzed using a statistical package for social science (SPSS). Results are presented narratively with a table or graph. It is concluded that there is a change in the ocular surface structure leading to the improvement of dry eye disease after the administration of topical 3% diquafosol based on TBUT, Schirmer, and OSDI indicators.